Preliminary analysis of red mud spill based on aerial imagery, Hungary - Burai, Péter; Smailbegovic, Amer; Lénárt, Csaba; Berke, József; Milics, Gábor; Tomor, Tamás; Bíró, Tibor (Acta Geographica Debrecina Landscape & Environment series, 2011)
One of the largest industrial spills in Europe occurred in the village of Kolontár (Hungary) on October 4, 2010. The primary objective of the hyperspectral remote sensing mission was to monitor that is necessary in order to estimate the environmental damage, the precise size of the polluted area, the rating of substance concentration in the mud, and the overall condition of the flooded district as soon as possible. The secondary objective was to provide geodetic data necessary for the high-resolution visual information from the data of an additional Lidar survey, and for the coherent modeling of the event. For quick assessment and remediation purposes, it was deemed important to estimate the thickness of the red mud, particularly the areas where it was deposited in a thick layer. The results showed that some of the existing tools can be easily modified and implemented to get the most out of the available advanced remote sensing data.